Femoral Artery Blood Flow and Microcirculatory Perfusion During Acute, Low-Level Functional Electrical Stimulation in Spinal Cord Injury. (October 2018) - Barton, Thomas J.; Low, David A.; Janssen, Thomas W.J.; Sloots, Maurits; Smit, Christof A.J.; Thijssen, Dick H.J.
Abstract : Objective: Functional electrical stimulation (FES) may help to reduce the risk of developing macrovascular and microvascular complications in people with spinal cord injury. Low-intensity FES has significant clinical potential because this can be applied continuously throughout the day. This study examines the acute effects of low-intensity FES using wearable clothing garment on vascular blood flow and oxygen consumption in people with spinal cord injury. Design: This was a cross-sectional observation study. Methods: Eight participants with a motor complete spinal cord injury received four 3-min unilateral FES to the gluteal and hamstring muscles. Skin and deep femoral artery blood flow and oxygen consumption were measured at baseline and during each bout of stimulation. Results: Femoral artery blood flow increased by 18.1% with the application of FES ( P = 0.02). Moreover, femoral artery blood flow increased further during each subsequent block of FES ( P = 0.004). Skin perfusion did not change during an individual block of stimulation ( P = 0.66). Skin perfusion progressively increased with each subsequent bout ( P < 0.001). There was no change in femoral or skin perfusion across time in the nonstimulated leg (all P > 0.05). Conclusion: Low-intensity FES acutely increased blood flow during stimulation, with a progressive increase across subsequent FES bouts. These observations suggest that continuous, low-intensity FES may represent a practical and effective strategy to improve perfusion and reduce the risk of vascular complications. Abstract : Supplemental digital content is available in the text.